Funkcjonowanie pacjentek chorych na raka piersi leczonych metodą radioterapii = The functioning of breast cancer patients treated with radiotherapy - Szadowska-Szlachetka, Zdzisława; Kapitan, Justyna; Pietraszek, Agata; Janczaruk, Marzena; Stanisławek, Andrzej; Łuczyk, Marta (Journal of Education, Health and Sport, 2016)
Szadowska-Szlachetka Zdzisława, Kapitan Justyna, Pietraszek Agata, Janczaruk Marzena, Stanisławek Andrzej, Łuczyk Marta. Funkcjonowanie pacjentek chorych na raka piersi leczonych metodą radioterapii = The functioning of breast cancer patients treated with radiotherapy. Journal of Education, Health and Sport. 2016;6(9):489-497. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.151606 http://ojs.ukw.edu.pl/index.php/johs/article/view/3857 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 16.09.2016. Funkcjonowanie pacjentek chorych na raka piersi leczonych metodą radioterapii The functioning of breast cancer patients treated with radiotherapy Zdzisława Szadowska-Szlachetka1, Justyna Kapitan2, Agata Pietraszek1,3, Marzena Janczaruk3, Andrzej Stanisławek1,3, Marta Łuczyk1 1. Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie 2. Absolwentka Wydziału Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3. Centrum Onkologii Ziemi Lubelskiej im. św. Jana z Dukli w Lublinie Streszczenie: Cel pracy: Określenie jakości życia oraz czynników wpływających na funkcjonowanie kobiet z rakiem piersi leczonych metodą radioterapii. Materiał i metody: Badaniami objęto grupę 109 kobiet. W badaniach posłużono się metodą sondażu diagnostycznego z techniką ankiety, z wykorzystaniem autorskiego kwestionariusza ankiety oraz standaryzowanych narzędzi EORTC QLQ–C30 oraz EORTC QLQ – BR23. Analizy statystyczne przeprowadzono przy użyciu programu STATISTICA 10.0, przyjmując poziom istotności p<0,05. Wyniki i wnioski: Pacjentki na średnim poziomie oceniają swoją jakość życia zakresie skal funkcjonalnych – najlepiej w zakresie funkcjonowania fizycznego, najniżej w zakresie funkcjonowania społecznego. Ocena perspektyw na przyszłość, obrazu własnego ciała, funkcjonowania seksualnego i satysfakcji seksualnej wypadła niekorzystnie – około 20 punktów na sto. W zakresie niekorzystnych objawów występujących w trakcie leczenia największe nasilenie dotyczyło biegunki i duszności, zaś najmniejsze znaczenie dla pacjentek miały problemy finansowe. Czynniki demograficzne różnicujące oceny badanych kobiet w zakresie różnych aspektów funkcjonowania to: wiek, stan cywilny, wykształcenie, sytuacja zawodowa oraz w mniejszym stopniu miejsce zamieszkania. Słowa kluczowe: jakość życia, nowotwory piersi, zdrowie kobiety, radioterapia Abstract Objective: Identifying the quality of life and the factors influencing the functioning of women with breast cancer treated with radiotherapy Material and methods: The survey included a group of 109 women. The diagnostic survey method was applied, with the use of a self-designed questionnaire and standardised tools: EORTC QLQ–C30 and EORTC QLQ – BR23. Statistical analyses were carried out with the STATISTICA 10.0 software, and the significance level was p < 0.05. Results and conclusions: The patients assessed their quality of life as medium in terms of functional scales – the most favourable assessments concerned the women's physical functioning, and they evaluated their social functioning the least positively. The women's assessment of their future perspectives, their body image, and sexual functioning and satisfaction was rather unfavourable – approx. 20 points out of 100. As far as the negative symptoms experienced during treatment are concerned, the most common were diarrhoea and shortness of breath. Financial problems were the least important for the patients. Demographic factors differentiating the assessments made by the surveyed women on various aspects of functioning were: age, marital status, education, occupational status and, to a lesser degree, place of residence. Key words: quality of life, breast neoplasms, women's health, radiotherapy